Exogenous insulin antibody syndrome presenting with concurrent hypoglycemia and hyperglycemia - Xiao-Po Wang; Yan Wu; Jing Wu; Ying-Zhao Liu; Hui Jiang (Medicine, 2026)
Rationale: Antibodies against therapeutic insulin cause paradoxical hypoglycemia, termed exogenous insulin antibody syndrome (EIAS). This first report of glargine-induced EIAS post-total pancreatectomy introduces mycophenolate mofetil (MMF) as a novel steroid-sparing therapy. Patient Concerns: A 75-year-old woman developed refractory nocturnal hypoglycemia with daytime hyperglycemia (HbA1c 8.6%) 3 months post-pancreatectomy during glargine therapy. Diagnoses: Hypoglycemia (glucose 2.83 mmol/L) featured undetectable C-peptide, elevated insulin (103 μU/mL), high insulin autoantibodies (74.95 coi, Reference range 0–1.0), and polyethylene glycol (PEG) precipitation-confirmed antibody-bound insulin, with a marked decline in insulin concentration relative to baseline values (88% decline). Interventions: Standard approaches (switching to aspart insulin, carbohydrate enrichment, degludec/acarbose triple regimen) failed; prednisone alleviated hypoglycemia but provoked hyperglycemia. Outcomes: Mycophenolate mofetil (MMF) eliminated hypoglycemia within 2 weeks, reducing antibodies to 35.4 coi. Conclusion: This inaugural case highlights EIAS as a cause of unexplained hypoglycemia in pancreatectomized patients. MMF warrants consideration as primary immunosuppressive therapy for EIAS. Lessons: This case highlights that EIAS is a rare but important cause of paradoxical hypoglycemia and hyperglycemia in insulin-treated patients. MMF can serve as an effective therapeutic agent.